Arduino Smart Home Design - Ali Hadi Hasan Mohammed AlAbedi; Haroon Rashid Hammood Al Dallal (Genius Journals, 2022)
Smart home design and home automation systems are spreading rapidly worldwide. Partly from the contribution of communication technology, the IoT gadgets are increasingly enabling homeowners to completely control any device or home gadgets through their mobile phone through an internet connection. Amid this, the presence of efficient gadgets like Arduino boards has made the process simpler and more costeffective. This paper is a complete guide of what role Arduino boards play in home automation and how these boards have made smart home designing simpler and convenient. It also extends to elaborate why Arduino is a smart innovation and better option which makes it stand out over other IoTs.
Keywords: Arduino; IoTs; home automation; smart home design